2014
DOI: 10.1186/1471-2458-14-634
|View full text |Cite
|
Sign up to set email alerts
|

What interventions are effective on reducing inequalities in maternal and child health in low- and middle-income settings? A systematic review

Abstract: BackgroundThe deadline for achieving Millennium Development Goals 4 and 5 is approaching, but inequalities between disadvantaged and other populations is a significant barrier for progress towards achieving these goals. This systematic review aims to collect evidence about the differential effects of interventions on different sociodemographic groups in order to identify interventions that were effective in reducing maternal or child health inequalities.MethodsWe searched the PubMed, EMBASE and other relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…The explanatory variables included; mother’s age at birth (in years, ordered), birth order, place of delivery (health facility delivery or other place, e.g., home), residence (urban or rural), maternal education and wealth status, maternal and paternal occupation, birth attendance during delivery (skilled attendance), ANC timing, marital status, distance to a health facility, and being told about pregnancy complications. These factors were found to be significantly associated with PNC utilization in studies done for example, in Nepal and Tanzania (13, 14). The outcome of interest was PNC utilization (either in the first 48 h or after 48 h following the delivery of the baby) by women aged 15–49 years who had a baby 2 years prior to the survey considering the most recent birth.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The explanatory variables included; mother’s age at birth (in years, ordered), birth order, place of delivery (health facility delivery or other place, e.g., home), residence (urban or rural), maternal education and wealth status, maternal and paternal occupation, birth attendance during delivery (skilled attendance), ANC timing, marital status, distance to a health facility, and being told about pregnancy complications. These factors were found to be significantly associated with PNC utilization in studies done for example, in Nepal and Tanzania (13, 14). The outcome of interest was PNC utilization (either in the first 48 h or after 48 h following the delivery of the baby) by women aged 15–49 years who had a baby 2 years prior to the survey considering the most recent birth.…”
Section: Methodsmentioning
confidence: 92%
“…The positive association of place of delivery with PNC services utilization could be attributed to the fact that women who gave their last birth in a health institution had greater opportunity to get exposed to health education related to PNC services at the time of delivery and thus get access to learn about the types, benefits and availabilities of PNC services during their stay in the health institutions (2). Many factors could explain an observation that a proportion of women did not deliver at health facilities and consequently reduced their chances of maternal PNC use in the first 48 h. Studies (13, 15) found out that the low level of complete PNC compliance may arise from a combination of structural determinants, such as poor access to services, perceived lack of services at such facilities by mothers, perceived lack of importance of seeking PNC services, a shortage of community providers making routine home visits, costs and transportation difficulties, and other cultural, geographic, or financial barriers. It was found out that even among the women who delivered in health facilities approximately 20% did not utilize PNC in the first 48 h after the birth of the baby.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews have highlighted innovative strategies for reducing such inequities to improve maternal and child health. 50 Finally, the state and international partners must support and protect women and children who are at risk of gender based violence, lack of economic security, and physical immobility. High rates of maternal and adolescent malnutrition remain tenacious underlying risk factors for ill health and mortality in the region.…”
Section: Health In South Asiamentioning
confidence: 99%
“…Evidence has shown the effectiveness of multidimensional approaches that may include conditional cash transfers, voucher schemes, microcredit, outreach services, and targeted community health services. 36 Innovations Improved delivery of child services will require continuous innovation, and the most promising innovations need to be supported, tested, used, and refined in countries. Innovations such as digital systems (including mobile health) have potential to strengthen health systems, reduce barriers to access, and strengthen monitoring and evaluation.…”
Section: Promoting Equitymentioning
confidence: 99%